First case of Candida auris infection in Belgium in a surgical patient from Kuwait. Issue 3 (3rd May 2020) - Dewaele, Klaas; Frans, Johan; Smismans, Annick; Ho, Erwin; Tollens, Tim; Lagrou, Katrien
ABSTRACT: Objective and importance: Candida auris is a relatively new yeast species and an emerging opportunistic pathogen. It was first reported in 2009 in East Asia, as a difficult-to-identify Candida species of uncertain clinical relevance. In recent years, it has appeared globally as a cause of invasive infections, not infrequently eliciting nosocomial outbreaks. Species identification in clinical laboratories has been challenging, as traditional phenotypic and biochemical methods have been generally unreliable. Clinical management is often complicated by multidrug resistance in many isolates. Additionally, C. auris has demonstrated an unusual ability for persistence in the hospital environment and in asymptomatic patients. We present the first Belgian case of C. auris infection along with a brief review of the literature.Clinical presentation: A patient was referred from Kuwait for surgical treatment after a complicated bariatric procedure. Few days after transferral, she developed a catheter-related blood stream infection with C. auris . We obtained a low-confidence identification of C. auris with the Bruker Biotyper MALDI-TOF MS system (Bruker Corporation, Billerica, MA, U.S.A.), and of Candida haemulonii with the Vitek YST identification system, version 7.01 (bioMérieux, Marcy-L'Etoile, France). Definite identification was obtained using Internal Transcribed Spacer (ITS) sequencing. As most C. auris isolates, our strain was resistant to fluconazole, and the patient was eventually treated with catheter removal and anidulafungin therapy. We documented persistence of C. auris clones with acquired echinocandin resistance in our patient up to 18 months after the infection.Conclusion: Clinicians and microbiologists should be aware of this globally emerging yeast, that poses important challenges in identification, treatment and hospital infection control.